Gravity and Friction in Growing East Asia - Gill, Indermit; Kharas, Homi (2012)
Without the advantages of low wages or high skills, East Asian economies are following a new path of regional integration, led by China. Along this path, policy-makers must manage a migration of 2 million people a month to East Asia's cities, a sharp and unprecedented increase in income inequality, and a growing discontent with corruption as governance structures have been decentralized. Having successfully integrated globally before the financial meltdown of the 1990s, and integrating regionally at an even faster pace since then, East Asia's middle-income countries must now accelerate a third integration, this time at home. Growth based on scale economies and specialization requires managing both gravity and friction. This article outlines what East Asian nations must do to manage these forces even as another financial meltdown is taking place. How well they can do this will determine whether they will grow through middle income to join the ranks of developed economies or not escape the 'middle-income trap'.